Organs-on-chips - Tung, Yi-Chung (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Recent advances in microsystems technology and cell culture techniques have led to the development of organ-on-chip microdevices that produce tissue-level functionality, not possible with conventional culture models, by recapitulating natural tissue architecture and microenvironmental cues within microfluidic devices.